Solution to an Optimal Control Problem via Canonical Dual Method - Jinghao Zhu; Jiani Zhou (Journal of Control Science and Engineering)
The analytic solution to an optimal control problem is investigated using the canonical dual method. By means of the Pontryagin principle and a transformation of the cost functional, the optimal control of a nonconvex problem is obtained. It turns out that the optimal control can be expressed by the costate via canonical dual variables. Some examples are illustrated.